Administracja publiczna w Niemczech wobec problemu restytucji dóbr kultury – problemy prawne i etyczne - Dobosz, Piotr (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
There are presented in the paper current problems of restitution of cultural goods looted by Hitler’s Germany in times of the II World War. Considerations include characteristics of legal and ethic facets. The are also discussed functions of authorities in Germany in scope of restitution of properties looted by Hitler’s troops.
Keywords: Land; Consultative Committee for the restitution of spoliated cultural property; status; Standing Conference of the Ministers of Cultural Affairs of the Länder in the Federal Republic of Germany; protection of monuments; German Lost Art Foundation based in Magdeburg; protection of monuments in Germany and in Poland; monument; protection; cultural heritage; heritage; law; restitution; legal; resulting from National Socialist/Nazi persecutions; work of art